Endometriosis and Uterine Fibroids (Leiomyomata): Comorbidity, Risks and Implications - Uimari, Outi; Nazri, Hannah; Tapmeier, Thomas (Frontiers in Reproductive Health, 2021)
Uterine Fibroids (leiomyomata) and endometriosis affect millions of women world-wide. Although aetiology and natural history of the conditions are markedly different, symptoms can overlap and make differential diagnoses necessary, often using invasive methods such as laparoscopy. Considerable comorbidity exists between the two conditions and needs to be taken into account when treating fibroids and/or endometriosis. The genetic foundations of both uterine fibroids and endometriosis remain to be fully understood but recent evidence suggest common underpinnings. Here, we discuss the comorbidity of uterine fibroids and endometriosis and the implications for diagnosis, treatment and risks.